DNA barcoding reveals an extensive number of cryptic introductions of bladed Bangiales (Rhodophyta) in the Southern North Sea - Knoop, Jessica; Bouckenooghe, Silke; van der Loos, Luna M.; D’hondt, Sofie; Karremans, Mart; Perk, Frank; Leliaert, Frederik; De Clerck, Olivier (Frontiers in Marine Science, 2024)
Using a DNA barcoding approach, we document an extensive number of inter-species cryptic introductions of bladed Bangiales (Pyropia) at an historic oyster aquaculture site in the Southern North Sea. We sampled the intertidal of 20 locations along the Belgian and Dutch coastline, ranging from sheltered to exposed, between February 2022 and April 2023 for bladed Bangiales. 230 individuals of bladed Bangiales were collected, morphological and ecological characteristics described and identified based on chloroplast rbcL gene sequences, revealing the presence of 13 species belonging to the genera Porphyra and Pyropia. While seven species (P. dioica, P. linearis, P. purpurea, P. umbilicalis, Py. collinsii, Py. elongata, Py. leucosticta) are regarded as native to the Northeast Atlantic, four species (Py. katadae, Py. koreana, Py. kinositae and Py. yezoensis) are considered non-indigenous. The records of Py. katadae, Py. kinositae and Py. koreana are the first confirmed observations for the Northeast Atlantic region. In addition, we identified two distinct rbcL clades, for which a definite species identification could not be established due to a lack of matching reference sequences. Species diversity was generally higher during winter and at exposed sites facing the open North Sea. The surprisingly high species diversity of the bladed Bangiales could only be revealed by molecular identification -a crucial tool for reliable species identification in this group of organisms.